"Keep it safe" : minimizing alcohol-related harm through street interventions - Jervis, Ros; Smith, Michelle ([London] : SAGE, 2016)
Wolverhampton City Primary Care Trust (PCT) is a legal organisation that launched a programme ("Keep it Safe") designed to solve issues emanating from alcohol abuse. In cooperation with multiple partners, the PCT had a number of goals for its new programme, including youth consultation, prevention of assault and violence, and domestic abuse. Following a number of campaigns and strategies to promote its mission, PCT marketers present us with the leading data they compiled from their thorough research using the marketing mix (the 4Ps: product, promotion, place, and price), and ultimately evaluate the effectiveness of their programme.
Originally Published in: French, J., Merritt, R., & Reynolds, L. (2011). "Keep It Safe": Minimizing Alcohol-related Harm Through Street Interventions. In Social marketing casebook (pp. 183-195). London: SAGE Publications Ltd. Print. ISBN: 9780857025449.
Description based on online resource; title from home page (viewed on April 8, 2016).
Keywords: elektronické knihy; electronic books; Drinking of alcoholic beverages -- Health aspects -- England -- Wolverhampton -- Case studies; Drinking of alcoholic beverages -- Social aspects -- England -- Wolverhampton -- Case studies; Social marketing -- Case studies